(untitled) (European Journal of Marketing and Economics, 2023)
Within health care projects for change and innovation, professionals should ambitiously cooperate in order to yield a creative multidisciplinary mindset for guaranteed innovative output. Failure of innovation projects is amongst others due to deterioration and insufficient focus on relational aspects. Aim; an innovative management tool for facilitating process innovation is launched. Methods; Systemic innovation (SI) is a social network management model, subsidiary to actual management models for quality improvement and innovation. The SI management model yields essential tools for stimulation of communication in multidisciplinary teams in order to shape alternative mindsets. Results; The key domains of SI representing socio-dynamics, value of arguments and flexibility for change concern topics for assessment of behavior with regard to psychosocial and organizational characteristics. The key domains yield a format enabling a critical appraisal concerning improvement of socio-technologic aspects in case of process innovation. Conclusion; SI yields a format for stimulation of social awareness with regard to self-assessment, interoperability and mindset generation in multidisciplinary teams of professionals.